The blind and the multimedia learning - Picelli Sanches, Emilia Christie; Bueno, Juliana; Leite Ribeiro Okimoto, Maria Lucia (InfoDesign, 2021)
It is a right to people with disabilities to have full access to information and learning environments. For blind learners, attention is required on how to transpose visual information to alternative sensory channels, without cognition overload. Thus, considering that blind people use auditory and tactile sense as alternatives to the visual channel, this article seeks to discuss blind people learning, from the perspective of Information Design and the Cognitive Theory of Multimedia Learning (CTML). Therefore, it is firstly sought to comprehend the Dual-Coding Theory and the Cognitive Theory of Multimedia Learning and, then, reflect on an adaptation of CTML to a blind context. Furthermore, it brings three examples of accessible materials to corroborate with the theoretical assumptions presented.